The East moves West India, China, and Asia's growing presence in the Middle East - Kemp, Geoffrey; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2010)
"Details the growing interdependence of the Middle East and Asia and its likely ramifications. Particular attention is given to India and China, which have a strong interest in trade--especially in oil and natural gas--with the Middle East and Central Asia"--Provided by publisher.
pt. 1. Introduction -- pt. 2. The key Asian players -- pt. 3. Strategic linkages.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Petroleum industry and trade -- Political aspects -- Middle East; Gas industry -- Political aspects -- Middle East; Middle East -- Foreign economic relations -- India; India -- Foreign economic relations -- Middle East; Middle East -- Foreign economic relations -- China; China -- Foreign economic relations -- Middle East; Electronic books